The Effectiveness of Olive Oil to Combat Lice in Pregnant Women and Children - Bafreen Mohamad Raza; Haifaa Mohammed Amin; Hanadi Abdul-Elah Abdul-Razzaq (Institute of Medico-legal Publications Pvt Ltd, 2021)
For the period from February 2019 until August 2019 it was checked 75 cases of pregnant women andchildren included girls and boys, and 28 pregnant women, 42 girls and 5 males were found to be infected. Head louse , as the study showed that the highest incidence of head louse was recorded among girls , itreached 56% , followed by pregnant women with a percentage of infection 37.33% , while males recordedless infection with head louse amounted to 6.66% , respectively , and olive oil was used to determine itseffectiveness to combat head louse as a natural substance , and it used Statistical analysis was used Dunkintest .